Pengaruh jenis latihan guru dan pengalaman mengajar terhadap efikasi guru sekolah menengah - Khalid Johari; Zurida Ismail; Shuki Osman; Ahmad Tajuddin Othman (penerbit ukm, 2009)
This research was aimed to determine the influence of teacher qualification factors, namely type of teacher training and teaching experience on secondary school teachers’ efficacy in Sabah. Data were collected using the Teachers’ Sense of Efficacy Scale which involved 928 teachers from 22 secondary school in four districts. ANOVA analysis found significant mean difference in all dimensions of teacher efficacy according to type of teacher training and teaching experience. Finding also showed that teachers with Diploma in Malaysian Education obtained the highest level of efficacy, compared to teachers from the other programs. Teachers with teaching more than seven years of teaching experience were statistically different in efficacy than those with less teaching experience. The research suggested that well-trained graduate teachers should be given more opportunity to teach in positive teaching environment to enable them to develop positive teacher efficacy.